Recontextualising employability in the Active Learning Classroom. Issue 2 (4th March 2021) - Roderick, Ian
ABSTRACT: Active Learning Classrooms (ALCs) are distinguishable by their inclusion of dedicated media technologies, shared tables and wheeled chairs, organised to promote small-group interaction in larger classes. While discursively presented as a panacea to presumed problems of 'effective' pedagogy, a multimodal discourse analysis of the ALC highlights how, in the context of discourses of employability and entrepreneurialism, it functions as an apparatus for normalising precarious forms of labour. The ALC should be properly understood as what Bernstein calls a pedagogic device in which knowledge, as the product of social relations, is recontextualised as educational knowledge and in turn becomes the basis for a new set of evaluative criteria. Accordingly, the ALC recontextualises 'the real world' and its prioritisation of so-called employable skills in the classroom and in doing so, further legitimises what can be termed, the proceduralisation of pedagogy into a simple repertoire of techniques that can be applied to deliver information to an albeit 'active' audience.